Hubungan Self Control dengan Kecanduan Game Online pada Mahasiswa Kampus V Universitas Negeri Padang - Muhammad Fahri Nasution; Siti Mardhiah; Diva shafira; Verlin Orva linnisa; Iqbal Rahman; Afifah Nur Hasanah (Journal of Health, Medical, and Psychological Studies, 2026)
Online game addiction is a behavioral disorder that is increasingly prevalent among university students and has the potential to impair academic performance, social functioning, and psychological well-being. This study aims to examine the relationship between self-control and online game addiction among students at Campus V of Universitas Negeri Padang. A quantitative approach with a correlational design was employed. The study involved 103 students selected using a purposive sampling technique. Data were collected using the Brief Self-Control Scale and the Game Addiction Scale, then analyzed using the Spearman rank correlation test with IBM SPSS Statistics 23. The findings revealed a significant negative relationship between self-control and online game addiction (rs = –0.514; p < 0.001). These results indicate that higher levels of self-control are associated with lower levels of online game addiction among university students. This study highlights the importance of strengthening self-control as a preventive strategy to reduce the risk of online game addiction in higher education settings.